Early detection of diabetic neuropathy by investigating CNFL and IENFD in thy1-YFP mice. Issue 2 (November 2016) - Leckelt, Janine; Guimarães, Pedro; Kott, Annett; Ruggeri, Alfredo; Stachs, Oliver; Baltrusch, Simone
Abstract : Small fiber neuropathy is one of the most common and painful long-term complications of diabetes mellitus. Examination of the sub-basal corneal nerve plexus is a promising surrogate marker of diabetic neuropathy. To investigate the efficacy, reliability and reproducibility of in vivo corneal confocal microscopy (IVCCM), we used thy1-YFP mice, which express yellow fluorescence protein (YFP) in nerve fibers. 4 weeks after multiple low-dose injections of streptozotocin, thy1-YFP mice showed manifest diabetes. Subsequent application of insulin-releasing pellets for 8 weeks resulted in a significant reduction of blood glucose concentration and HbA1c, a significant increase in body weight and no further increase in advanced glycation end products (AGEs). IVCCM, carried out regularly over 12 weeks and analyzed both manually and automatically, revealed a significant loss of corneal nerve fiber length (CNFL) during diabetes manifestation and significant recovery after insulin therapy. Ex vivo analyses of CNFL by YFP-based microscopy confirmed the IVCCM results (with high sensitivity between manual and automated approaches) but demonstrated that the changes were restricted to the central cornea. Peripheral areas, not accessible by IVCCM in mice, remained virtually unaffected. Because parallel assessment of intraepidermal nerve fiber density revealed no changes, we conclude that IVCCM robustly captures early signs of diabetic neuropathy.